A nitrogen-doped porous graphene and its preparation method and application

By improving the Hummer’s method, the preparation of nitrogen-doped porous graphene was solved, and the problem of small specific surface area and low nitrogen content in the prior art was solved, and the effect of efficient catalytic reduction of aromatic nitro compounds was achieved.

CN115974056BActive Publication Date: 2025-03-18展长振

Patent Information

Application Number
CN202211317485.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2025-03-18
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The existing nitrogen-doped porous graphene has a small specific surface area and a low nitrogen content, so it is impossible to efficiently catalyze the reduction of aromatic nitro compounds.

Method used

Graphene oxide aerogel was prepared by the improved Hummer’s method and was uniformly dispersed with the nitrogen-containing precursor and activator. Nitrogen-doped porous graphene was prepared by drying and high-temperature calcination.

Benefits of technology

The prepared nitrogen-doped porous graphene has a large specific surface area, developed pores and high nitrogen content, and has far better catalytic activity than existing catalysts. It can efficiently reduce aromatic nitro compounds in aqueous solution under mild conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115974056B_ABST
    Figure CN115974056B_ABST
Patent Text Reader

Abstract

The present invention discloses a nitrogen-doped porous graphene and a preparation method and application thereof. The preparation method comprises the following steps: uniformly dispersing graphene oxide aerogel, a nitrogen-containing precursor and an activator in deionized water, followed by drying and high-temperature calcination to obtain nitrogen-doped porous graphene; wherein the nitrogen-containing precursor is selected from at least one of urea, melamine and ammonium hydroxide; and the activator is selected from at least one of KFeO4 and KOH. The present invention uses KOH and KFeO4 as activators, and urea, melamine and ammonium hydroxide as nitrogen sources to simply and efficiently prepare nitrogen-doped porous graphene. The obtained nitrogen-doped porous graphene has a large specific surface area, developed pores and a high nitrogen content. When applied to the catalytic reduction of aromatic nitro compounds, its catalytic activity is far superior to the catalysts reported in the literature, including metal catalysts and carbon-based metal-free catalysts. It can efficiently reduce aromatic nitro compounds in aqueous solution under mild conditions, and also has the advantages of low cost and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphene catalytic materials, and in particular to nitrogen-doped porous graphene and a preparation method and application thereof. Background Art

[0002] Aromatic nitro compounds are an important class of chemical raw materials, which are widely used in the production of medicines, pesticides, herbicides, dyes, explosives and other chemical products. Because of their high toxicity, they will remain in the soil for a long time and are one of the most difficult organic pollutants to degrade. Using sodium borohydride (NaBH4) as a reducing agent, the reduction of aromatic nitro compounds is considered to be the greenest and most economical method from an environmental and industrial perspective. In the absence of a catalyst, NaBH4 cannot effectively reduce aromatic nitro compounds due to kinetic barriers. Therefore, efforts should be made to develop effective catalysts to enhance this conversion reaction. Most of the existing catalysts for reducing aromatic nitro compounds are metal-based catalysts. Although these metal-based catalysts show good catalytic activity and product selectivity, their commercial practicality is hindered by high cost, limited resources and metal leaching during the catalytic process. Therefore, alternatives to metal catalysts should be developed.

[0003] Carbon materials are potential substitutes for metal catalysts due to their low price, good stability, good biocompatibility, environmental friendliness and easy availability. Graphene is one of the most notable carbon materials. It has a unique two-dimensional planar structure and is a single-atom-thick carbon material separated from graphite. Graphene has a large specific surface area and ultra-high electron mobility, as well as high thermal and electrical conductivity. These unique properties enable it to be used in metal-free carbon-catalyzed reduction of aromatic nitro compounds.

[0004] Nitrogen doping can destroy the chemical inertness of graphene by changing the electronic configuration, converting it into a highly active catalyst with catalytic applications. Patent (CN113479872A) discloses a method for preparing nitrogen-doped three-dimensional porous graphene hydrogel by hydrothermal method, which uses urea as a nitrogen source and hydrogen peroxide as an activator. The prepared nitrogen-doped three-dimensional porous graphene hydrogel is a high-performance electrode material. Patent (CN110606480A) discloses a method for preparing nitrogen-doped porous graphene by hydrothermal and high-temperature calcination method. The prepared nitrogen-doped porous graphene has high redox activity and is applied to the field of fuel cells. Patent (CN109911887A) discloses a method for preparing nitrogen-doped porous graphene by using aniline as a nitrogen source and adding surfactants, metal salts, etc. The prepared nitrogen-doped porous graphene is applied to the field of supercapacitors. The above patents (CN113479872A, CN110606480A) use H2O2 as a pore-forming agent, and patent CN109911887A prepares nitrogen-doped porous graphene by adding surfactants, metal salts and high-temperature calcination. The specific surface area of ​​the obtained products is small, the nitrogen content is low, and they are only used in the field of energy storage. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a nitrogen-doped porous graphene and a preparation method and application thereof, and solve the technical problem in the prior art that nitrogen-doped porous graphene has a small specific surface area and a low nitrogen content and cannot be used for efficient catalytic reduction of aromatic nitro compounds.

[0006] A first aspect of the present invention provides a method for preparing nitrogen-doped porous graphene, comprising the following steps:

[0007] Graphene oxide suspension was prepared by improving Hummer's method, and graphene oxide aerogel was obtained by freeze drying.

[0008] The graphene oxide aerogel, the nitrogen-containing precursor and the activator are uniformly dispersed in deionized water, and then dried and calcined at high temperature to obtain nitrogen-doped porous graphene; wherein,

[0009] The nitrogen-containing precursor is selected from at least one of urea, melamine and ammonium hydroxide;

[0010] The activator is selected from at least one of KFeO4 and KOH.

[0011] The second aspect of the present invention provides a nitrogen-doped porous graphene, which is obtained by the preparation method of the nitrogen-doped porous graphene provided by the first aspect of the present invention.

[0012] A third aspect of the present invention provides an application of nitrogen-doped porous graphene, wherein the nitrogen-doped porous graphene is applied to the efficient catalytic reduction of aromatic nitro compounds.

[0013] Compared with the prior art, the beneficial effects of the present invention include:

[0014] The present invention uses KOH and KFeO4 as activators and urea, melamine and ammonium hydroxide as nitrogen sources to simply and efficiently prepare nitrogen-doped porous graphene. The obtained nitrogen-doped porous graphene has a large specific surface area, developed pores and a high nitrogen content. When applied to the catalytic reduction of aromatic nitro compounds, its catalytic activity is far superior to catalysts reported in the literature, including metal catalysts and carbon-based metal-free catalysts. It can efficiently reduce aromatic nitro compounds in aqueous solutions under mild conditions, and also has the advantages of low cost and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a scanning electron microscope image of the nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0016] Figure 2 TEM image of nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0017] Figure 3 is an X-ray photoelectron spectrum of the nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0018] Figure 4 is the nitrogen adsorption isotherm of the nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0019] Figure 5 is a pore size distribution diagram of the nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0020] Figure 6 This is an ultraviolet spectrum of the catalytic reduction of 4-nitrophenol by the nitrogen-doped porous graphene prepared in Example 1 of the present invention;

[0021] Figure 7 This is a performance comparison chart of the catalytic reduction of 4-nitrophenol by the nitrogen-doped porous graphene prepared in Examples 1, 2, 3, and 4 of the present invention;

[0022] Figure 8 This is a comparison chart of the catalytic reduction performance of the nitrogen-doped porous graphene prepared in Example 8 and Example 9 of the present invention for catalytic reduction of p-nitroaniline and p-nitrotoluene, respectively. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0024] A first aspect of the present invention provides a method for preparing nitrogen-doped porous graphene, comprising the following steps:

[0025] S1. preparing a graphene oxide suspension by an improved Hummer's method, and obtaining a graphene oxide aerogel by freeze drying;

[0026] S2. The graphene oxide aerogel, the nitrogen-containing precursor and the activator are uniformly dispersed in deionized water, and then dried and calcined at high temperature to obtain nitrogen-doped porous graphene.

[0027] In the present invention, the step of preparing the graphene oxide suspension by improving Hummer's method comprises:

[0028] S11. Mix the ultrafine graphite and the mixed acid solution uniformly to obtain a mixed solution A; wherein the mixed acid solution is a mixed solution of concentrated sulfuric acid and concentrated phosphoric acid, and the volume ratio of concentrated sulfuric acid to concentrated phosphoric acid is (8-10):1, further 9:1; the particle size of the ultrafine graphite is 5-30 μm; the amount ratio of the ultrafine graphite to the mixed acid solution is 1 g: (100-150) mL, further 1 g: (130-140) mL.

[0029] S12, placing the mixed solution A in an ice bath, and slowly adding potassium permanganate thereto to obtain a mixed solution B; wherein the mass ratio of the ultrafine graphite to potassium permanganate is 1:(4-8), further 1:6.

[0030] S13, reacting the mixed solution B at a temperature of 45 to 55° C. for 10 to 14 hours, and then cooling to room temperature to obtain a mixed solution C;

[0031] S14, pouring the mixed solution C onto ice cubes, stirring evenly, adding hydrogen peroxide during stirring until the system changes color, and obtaining a graphene oxide suspension, wherein the mass concentration of hydrogen peroxide is 25% to 30%, and the amount ratio of ultrafine graphite to hydrogen peroxide is 1g: (2 to 4)mL.

[0032] In the present invention, before freeze drying, the graphene oxide suspension needs to be repeatedly washed with dilute acid and deionized water and filtered.

[0033] In the present invention, the nitrogen-containing precursor is selected from at least one of urea, melamine and ammonium hydroxide, and the mass ratio of the nitrogen-containing precursor to the graphene oxide aerogel is (3-8):1, further 5:1.

[0034] In the present invention, the activator is selected from at least one of KFeO4 and KOH, and the mass ratio of the activator to the graphene oxide aerogel is (0.5-3):1, further (1-2.5):1, and further 2:1.

[0035] In the present invention, the drying process is carried out in a blast dryer, the drying temperature is 50-100° C., and the drying time is 8-16 hours.

[0036] In the present invention, calcination is carried out under an inert gas atmosphere, and the inert gas includes but is not limited to nitrogen and argon; the temperature of high-temperature calcination is 700-1000°C, for example, it can be 700°C, 800°C, 900°C, 1000°C, etc., and the present invention is not limited to this; the time of high-temperature calcination is 1-5h, for example, it can be 1h, 2h, 3h, 4h, 5h, etc., and the present invention is not limited to this; the heating rate is 3-5°C / min.

[0037] In the present invention, after the calcination is completed, the calcined product needs to be repeatedly washed with dilute acid and deionized water and filtered, and then vacuum dried to obtain nitrogen-doped porous graphene. The temperature of the vacuum drying oven is 50-80° C., and the time is 12-24 hours.

[0038] The second aspect of the present invention provides a nitrogen-doped porous graphene, which is obtained by the preparation method of the nitrogen-doped porous graphene provided by the first aspect of the present invention.

[0039] A third aspect of the present invention provides an application of nitrogen-doped porous graphene, wherein the nitrogen-doped porous graphene is applied to the efficient catalytic reduction of aromatic nitro compounds.

[0040] In the present invention, the above-mentioned aromatic nitro compounds include but are not limited to 4-nitrophenol, p-nitroaniline and p-nitrotoluene.

[0041] In the present invention, the reducing agent is sodium borohydride.

[0042] In the present invention, the process of applying the nitrogen-doped porous graphene to the efficient catalytic reduction of aromatic nitro compounds is carried out at room temperature.

[0043] In some specific embodiments of the present invention, the step of applying the nitrogen-doped porous graphene to the efficient catalytic reduction of aromatic nitro compounds comprises:

[0044] Dispersing nitrogen-doped porous graphene in deionized water to form a nitrogen-doped porous graphene dispersion;

[0045] dissolving an aromatic nitro compound in deionized water to form an aromatic nitro compound aqueous solution;

[0046] The nitrogen-doped porous graphene dispersion and sodium borohydride are added into the aromatic nitro compound aqueous solution for mixed reaction to catalyze the reduction of the aromatic nitro compound in water.

[0047] Among them, the concentration of the nitrogen-doped porous graphene dispersion is 1-3 mg / mL, further 2 mg / mL, and the volume is 1-10 μL, further 2 μL; the concentration of the aromatic nitro compound is 0.1-0.5 mM, further 0.2 mM, and the volume is 1-10 mL, further 3.5 mL; the molar ratio of sodium borohydride to the aromatic nitro compound is (100-1000):1, further 800:1.

[0048] To avoid redundancy, in the following embodiments of the present invention, graphene oxide is prepared by a modified Hummer's method, and the specific steps are as follows:

[0049] 1.5 g of ultrafine graphite was mixed with 180 mL of concentrated sulfuric acid and 20 mL of concentrated phosphoric acid, the obtained mixed solution was placed in an ice bath, and 9 g of potassium permanganate was slowly added thereto; the obtained mixed solution was placed in a constant temperature water bath for reaction for 12 h, during which the temperature was maintained at 50 ° C; after the above reaction system was cooled to room temperature, it was poured onto ice cubes and stirred evenly with a magnetic stirrer, and 5 mL of 30% hydrogen peroxide was added during the stirring process until the system changed color, thereby obtaining a graphene oxide suspension; it was repeatedly washed with dilute hydrochloric acid and deionized water and filtered, and finally dried with a vacuum freeze dryer to obtain a graphene oxide aerogel.

[0050] Example 1

[0051] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 2 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0052] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0053] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 4-nitrophenol was dissolved in deionized water to form a 4-nitrophenol solution with a concentration of 0.2 mM; 3.5 mL of the above 4-nitrophenol solution was added to a quartz cuvette at room temperature, and then 21.2 mg of sodium borohydride (solid) was added, and the two were mixed evenly by ultrasonication for 10 min, and then 2 μL of the above nitrogen-doped porous graphene dispersion was drawn with a microsyringe and injected into the mixed system for reaction, and the absorbance (400 nm) of 4-nitrophenol was detected by ultraviolet every few minutes.

[0054] Figure 1 and Figure 2The following are SEM and TEM images of nitrogen-doped porous graphene prepared in Example 1 of the present invention, respectively. Figure 1 and Figure 2 It can be seen that the prepared nitrogen-doped porous graphene has a highly wrinkled layer structure. Figure 3 This is an X-ray photoelectron spectrum of the nitrogen-doped porous graphene prepared in Example 1 of the present invention. It can be seen that an obvious nitrogen doping peak appears, and the nitrogen content is 5.67 at %. Figure 4 is the nitrogen adsorption isotherm of the nitrogen-doped porous graphene prepared in Example 1 of the present invention, Figure 4 It can be seen that nitrogen-doped porous graphene exhibits a high adsorption capacity for nitrogen, with a specific surface area of ​​780 m 2 / g. Figure 5 3 is a pore size distribution diagram of the nitrogen-doped porous graphene prepared in Example 1 of the present invention. It can be seen from the figure that the main pores of the nitrogen-doped porous graphene prepared according to the method of Example 1 are micropores and mesopores. Figure 6 The ultraviolet spectrum of the nitrogen-doped porous graphene prepared in Example 1 of the present invention for catalytic reduction of 4-nitrophenol. Figure 6 It can be seen that the prepared nitrogen-doped porous graphene has a high catalytic activity for the reduction of 4-nitrophenol, and can completely convert 4-nitrophenol into 4-aminophenol within 2 min, with a conversion frequency of 8.75×10 -2 mmol·mg -1 ·min -1 .

[0055] Example 2

[0056] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 2.5 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0057] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0058] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0059] Example 3

[0060] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 1.5 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0061] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0062] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0063] Example 4

[0064] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 1 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0065] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0066] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0067] Figure 7 The catalytic reduction performance comparison diagram of nitrogen-doped porous reduced graphene oxide prepared in Examples 1, 2, 3, and 4 of the present invention. Figure 4 It can be seen that the catalytic performance increases with the increase of activator, but when the activator increases to a certain extent, the catalytic performance will tend to decrease.

[0068] Example 5

[0069] (1) Weigh 1 g of graphene oxide aerogel, 5 g of melamine and 2 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0070] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 900°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0071] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0072] Example 6

[0073] (1) Weigh 1 g of graphene oxide aerogel, 5 g of melamine and 2 g of KFeO4 and disperse them in 30 mL of deionized water and stir them evenly with magnetic stirring;

[0074] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 900°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0075] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0076] Example 7

[0077] (1) Weigh 1 g of graphene oxide aerogel, 5 g of ammonium hydroxide and 1 g of KFeO4 and disperse them in 30 mL of deionized water and stir them evenly with magnetic stirring;

[0078] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 900°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0079] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of 4-nitrophenol, wherein the concentration of 4-nitrophenol was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0080] Example 8

[0081] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 2 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0082] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0083] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of p-nitroaniline, wherein the concentration of p-nitroaniline was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0084] Example 9

[0085] (1) Weigh 1 g of graphene oxide aerogel, 5 g of urea and 2 g of potassium hydroxide and disperse them in 30 mL of deionized water, and stir them evenly with a magnetic stirrer;

[0086] (2) The obtained mixed system was transferred to a nickel crucible, placed in an oven, and dried at 80°C for 12 hours. The obtained mixed system was placed in a tube furnace, and the temperature was raised to 800°C at 5°C / min in a nitrogen atmosphere, and kept warm for 3 hours. After cooling to room temperature, it was taken out, repeatedly washed with dilute hydrochloric acid and deionized water, filtered, and finally dried in a vacuum drying oven at 60°C for 24 hours to obtain a nitrogen-doped porous graphene catalyst;

[0087] (3) The nitrogen-doped porous graphene obtained above was dispersed in deionized water to form a nitrogen-doped porous graphene dispersion with a concentration of 2 mg / mL; 2 μL of the nitrogen-doped porous graphene dispersion was taken for catalytic reduction of p-nitrotoluene, wherein the concentration of p-nitrotoluene was 0.2 mM, the volume was 3.5 mL, and the amount of sodium borohydride was 21.2 mg.

[0088] Figure 8 This is a performance diagram of the nitrogen-doped porous graphene prepared according to Examples 8 and 9 of the present invention applied to the catalytic reduction of p-nitroaniline and p-nitrotoluene. It can be seen from the diagram that the prepared nitrogen-doped porous graphene has very high performance for the catalytic reduction of p-nitroaniline and p-nitrotoluene.

[0089] Compared with the prior art, the beneficial effects of the present invention also include:

[0090] (1) The present invention mixes graphene oxide with a nitrogen-containing monomer and an activator, and performs nitrogen doping and activation by high-temperature calcination. The nitrogen content of the obtained nitrogen-doped porous graphene is as high as 5 to 8 at.%, and the pores contained are mainly micropores and mesopores. The pore size of the micropores is mainly distributed between 0.6 and 2 nm, and the pore size of the mesopores is mainly distributed between 2 and 15 nm. The specific surface area is 300 to 1000 m 2 / g.

[0091] (2) Compared with nitrogen-doped porous graphene catalysts prepared by other methods, the nitrogen-doped porous graphene prepared according to the present invention has a high nitrogen content and a high specific surface area, and is applied to the catalytic reduction of aromatic nitro compounds for the first time, and has extremely high catalytic reduction performance, with a conversion frequency of up to 8.75×10 -2 mmol·mg -1 ·min -1 , which is much better than the catalysts reported in the literature.

[0092] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An application of nitrogen-doped porous graphene, characterized in that: The nitrogen-doped porous graphene is used for efficient catalytic reduction of aromatic nitro compounds, and the preparation method of the nitrogen-doped porous graphene comprises the following steps: Graphene oxide suspension was prepared by improving Hummer's method, and graphene oxide aerogel was obtained by freeze drying. The graphene oxide aerogel, the nitrogen-containing precursor and the activator are uniformly dispersed in deionized water, and then dried and calcined at high temperature to obtain nitrogen-doped porous graphene; wherein, The nitrogen-containing precursor is selected from at least one of urea, melamine and ammonium hydroxide; The activator is KOH, the mass ratio of the nitrogen-containing precursor to the graphene oxide aerogel is 5:1, and the mass ratio of the activator to the graphene oxide aerogel is 2:

1.

2. The use of nitrogen-doped porous graphene according to claim 1, characterized in that: The step of preparing the graphene oxide suspension by improving Hummer's method comprises: The ultrafine graphite and the mixed acid solution are mixed evenly to obtain a mixed solution A; The mixed solution A is placed in an ice bath, and potassium permanganate is slowly added thereto to obtain a mixed solution B; The mixed solution B was reacted at 45-55°C for 10-14 h, and then cooled to room temperature to obtain a mixed solution C; Pour the mixed solution C onto ice cubes and stir evenly. During the stirring process, add hydrogen peroxide until the system changes color to obtain a graphene oxide suspension.

3. The use of nitrogen-doped porous graphene according to claim 2, characterized in that: The mixed acid solution is a mixed solution of concentrated sulfuric acid and concentrated phosphoric acid, and the volume ratio of concentrated sulfuric acid to concentrated phosphoric acid is (8-10):1, the particle size of the ultrafine graphite is 5-30 μm; the dosage ratio of the ultrafine graphite to the mixed acid solution is 1 g: (100-150) mL; the mass ratio of the ultrafine graphite to potassium permanganate is 1: (4-8); the mass concentration of the hydrogen peroxide is 25%-30%, and the dosage ratio of the ultrafine graphite to hydrogen peroxide is 1 g: (2-4) mL.

4. The use of nitrogen-doped porous graphene according to claim 1, characterized in that: The high-temperature calcination is carried out in an inert gas atmosphere, the temperature of the high-temperature calcination is 700-1000° C., the time of the high-temperature calcination is 1-5 h, and the heating rate is 3-5° C. / min.

5. An application of the nitrogen-doped porous graphene according to claim 4, characterized in that: The step of applying nitrogen-doped porous graphene to the efficient catalytic reduction of aromatic nitro compounds comprises: Dispersing nitrogen-doped porous graphene in deionized water to form a nitrogen-doped porous graphene dispersion; dissolving an aromatic nitro compound in deionized water to form an aromatic nitro compound aqueous solution; The nitrogen-doped porous graphene dispersion and sodium borohydride are added to the aromatic nitro compound aqueous solution for mixed reaction to catalyze the reduction of the aromatic nitro compound in water; wherein, The concentration of the nitrogen-doped porous graphene dispersion is 1-3 mg / mL, and the volume is 1-10 μL; The concentration of the aromatic nitro compound is 0.1-0.5 mM, and the volume is 1-10 mL; The molar ratio of the sodium borohydride to the aromatic nitro compound is (100-1000):1.

Citation Information

Patent Citations

  • Nitrogen-doped porous graphene preparation method

    CN109911887A

  • Nitrogen-doped porous graphene and preparation method thereof

    CN110606480A

  • Preparation method of nitrogen-doped three-dimensional porous graphene hydrogel electrode material, electrode and application thereof

    CN113479872A

Cited By

  • Nitrogen doping method of gamma-graphdiyne and application of nitrogen doping method

    CN122010109A